Oncogene expression in primary myelodysplasia: correlation with haematological, karyotypic, and clinical progression. Issue 4 (April 1992) - Hutchinson, R M; Pringle, J H; Knight, S C; Lauder, I; Potter, A; Jagger, C
Abstract : AIMS: To see if the relative expressions of proto-oncogenes that are increased in acute myeloid leukaemia are raised in patients with myelodysplastic syndromes (MDS), and to see if they increase with progression to leukaemia. To note if there is a correlation between morphology, karyotype, and these proto-oncogene expressions and if any one proto-oncogene can predict prognosis. METHOD: Bone marrow from 130 patients was analysed at six monthly intervals over two years for relative mRNA expression of seven oncogenes, karyotype, and morphology. The technique used slot blot hybridisation and densitometric analysis. The results were compared with 14 surgical controls and 30 people with vitamin deficiency anaemia. RESULTS: Six of seven oncogenes showed increased expression which progressed with time, but did not correlate with morphological or karyotypic changes. Expression of four of the seven oncogenes was increased in megaloblastic and iron deficiency anaemia. C-mos showed differences among the five morphological subgroups; it correlated with abnormal location (p = 0.025) and seemed to influence prognosis. CONCLUSION: Increased proto-oncogenes reflect the overall marrow perturbation in MDS. C-mos may reflect persistence of monocyte pathway which confirms marrow stability.